Experimental investigations on inclined pullout behaviour of geogrids anchored in trenches. Issue 5 (18th September 2019) - Bhowmik, R.; Shahu, J. T.; Datta, M.
Abstract : Stability of geosynthetics along slopes in covers and liners of landfills depends partly on their tensile strength and partly on the efficiency of anchors holding the geosynthetics at berms or the top of the slope. The pull induced in these geosynthetics is in an inclined direction parallel to the slope. But due to difficulty in modelling inclined pullout behaviour experimentally, very few studies have so far been conducted on geosynthetics embedded in anchor trenches. This paper presents details of a device that can perform inclined pullout tests on geosynthetics at variable inclinations. Since geogrids are widely used as veneer reinforcement, inclined pullout tests are conducted on geogrids embedded in run-out, I-type and L-type anchors in sand. The maximum pullout force in the geogrid increases by more than 20% as the pull inclination increases from 0° to 20° in all the three types of anchors. The geogrids exhibit markedly different force-displacement behaviour for the three types of anchors, though the length of reinforcement remains the same. The peak pullout force for the I-type anchor was 1.6–1.7 times higher, and that for the L-type anchor was 2 times higher than that of the run-out anchor at all pullout inclinations.